2003
DOI: 10.1128/jcm.41.3.1259-1262.2003
|View full text |Cite
|
Sign up to set email alerts
|

Casein Agar: a Useful Medium for Differentiating Candida dubliniensis from Candida albicans

Abstract: Production of chlamydospores on casein agar at 24°C for 48 h provides a simple means for differentiating Candida dubliniensis from Candida albicans based on chlamydospore production. Of 109 C. dubliniensis isolates tested on this medium, 106 (97.2%) produced abundant chlamydospores and three produced few chlamydospores. In contrast, of the 120 C. albicans isolates tested, 111 (92.5%) failed to produce any chlamydospores, whereas the remaining nine isolates produced few chlamydospores. These findings indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…(v) Fourier transform infrared spectroscopy analysis of all cell components present in a cell can phenotypically discriminate these two species (31). More recently, it was reported that the two species could be distinguished by culture on Staib agar, Pal's agar, modified Pal's agar, and casein agar, on which only C. dubliniensis produces abundant chlamydospores and rough colonies (1,2,3,24,28). We also described an immunochromatographic assay differentiating between C. albicans and C. dubliniensis, but C. dubliniensis was identified only by default, owing to the specificity of the monoclonal antibodies (MAbs) (19).…”
mentioning
confidence: 99%
“…(v) Fourier transform infrared spectroscopy analysis of all cell components present in a cell can phenotypically discriminate these two species (31). More recently, it was reported that the two species could be distinguished by culture on Staib agar, Pal's agar, modified Pal's agar, and casein agar, on which only C. dubliniensis produces abundant chlamydospores and rough colonies (1,2,3,24,28). We also described an immunochromatographic assay differentiating between C. albicans and C. dubliniensis, but C. dubliniensis was identified only by default, owing to the specificity of the monoclonal antibodies (MAbs) (19).…”
mentioning
confidence: 99%
“…DRS has been reported in more than 60% of denture wearers, and although it is typically asymptomatic, it occasionally associates with leukoplakia, pseudomembrane formation, erythema and angular cheilitis (4,6,7).…”
mentioning
confidence: 99%
“…Candida dubliniensis has recently been isolated fromthe oral cavity ofhuman immunodeficiencyvirus (HIV)-infected patients, leading to its consideration as a novel, emerging, opportunistic pathogen (4). Candida colonization and biofilm formation on dentures may depend on oral hygiene practices, such as overnight denture removal, denture cleanser use, smoking and specific denture characteristics (5).…”
mentioning
confidence: 99%
“…The remaining 131 yeast strains were clinical isolates of oral, vaginal, sputum, or blood origin previously isolated at our laboratory and included 95 C. dubliniensis strains, 29 C. albicans strains, 2 C. krusei strains, 2 C. glabrata strains, 2 C. guilliermondii strains, and 1 C. parapsilosis strain. Clinical isolates were identified by their carbohydrate assimilation patterns on ID 32C strips (bioMérieux, Marcy-l'Etoile, France), growth at 42 to 45°C, chlamydospore production in casein agar (7), and indirect immunofluorescence with a specific anti-C. dubliniensis serum (2). Genotypic identification of C. dubliniensis and C. albicans isolates was performed by PCR with specific primers.…”
mentioning
confidence: 99%